Consuming race - Pitcher, Ben (London Routledge, 2014)
"This book explores how the ideas we have about race are produced and reproduced in everyday acts of consumption, and gives us a new way of thinking about the centrality of race to our lives. It argues that consumption is not a superficial leisure activity, but plays a very important role in shaping our beliefs about others: it is through the products we buy, the games we play, the TV we watch, the restaurants we eat at, the charities we give to and the holidays we take that we make sense of other groups and cultures. It is also through acts of racial consumption that we communicate our own identities, and express our fears and desires. Providing an accessible and highly readable overview of the latest research, an introduction to critical methodologies, and a detailed reading of a range of images, texts, products, sites and artifacts, Consuming Race gives students of sociology, media and cultural studies the opportunity to make connections between academic debates and their own everyday practices of consumption"-- Provided by publisher.
"From the products we buy to the television we watch, new media, books, food, design, toys and games, plants, animals and landscapes are all saturated with racial meanings. By consuming race in these various forms, we make sense of other groups and cultures, communicate our own identities, express our needs and desires, and discover new ways of thinking and being. This book explores how the meanings of race are made and remade in acts of creative consumption. Ranging across the terrain of popular culture, and finding race in some unusual and unexpected places, it offers fresh and innovative ways of thinking about the centrality of race to our lives. Consuming Race provides an accessible and highly readable overview of the latest research and a detailed reading of a diverse range of objects, sites and practices. It gives students of sociology, media and cultural studies the opportunity to make connections between academic debates and their own everyday practices of consumption"-- Provided by publisher.
Includes bibliographical references (pages 153-167) and index.
Keywords: African American consumers; Consumers, Black; Consumers; Race -- Social aspects